Psychological Conflict Of The Main Character Portrayed In Sam Levinson™s Movie Series: Euphoria - Sinaga, Gusnida Rezeky; Saragih, Amrin (Universitas Negeri Medan, 2023)
This study is concerned with Psychological conflicts experienced by the main character in Sam Levinson's movie series